Uji Efektifitas Pupuk Organik Dari Limbah Kulit Durian dan Pupuk NPK Terhadap Pertumbuhan Tanaman Jagung Manis (Zea mays saccharata Sturt) di Perkebunan IKDS Tembung - Komar Maulid Dongoran; Dini Mufriah; Syahriandi Akbari (UNIVERSITAS LABUHANBATU, 2026)
Sweet corn (Zea mays saccharata Sturt) is one of the second largest food crops in Indonesia cultivated after rice. Sweet corn has nutritional content as a staple food substitute for rice. Sweet corn plants require complete nutrients, namely macro and micro nutrients with a balanced composition. Efforts made to increase the production and quality of sweet corn plants are carried out by using durian peel compost and NPK fertilizer. The purpose of this study was to determine the effect of the effectiveness of organic fertilizer from durian peel waste and NPK fertilizer and the interaction between the two treatments on the growth of sweet corn plants (Zea Mays Saccharata Sturt). This study used a factorial completely randomized design consisting of 2 factors. The first factor is durian peel compost (K) consisting of 4 levels and the second factor is: NPK fertilizer 16:16: (N) consisting of 4 levels so that 16 treatment combinations were obtained. Each treatment combination was repeated 3 times so that a total of 48 experimental units. Each plot consists of 4 plants and 2 plants in the field as observation samples, so that the total number of plants is 192 plants. The treatment factors are Durian peel compost fertilizer dosage factor (D) consisting of 4 levels, namely: D0 = Without durian peel compost, D1 = Durian peel compost 1 kg / plot (10 tons / ha), D2 = Durian peel compost 2 kg / plot (20 tons / ha), D3 = Durian peel compost 3 kg / plot (30 tons / ha), NPK 16:16:16 fertilizer dosage factor (N) consists of 4 levels, namely: N0 = Without NPK fertilizer, N1 = NPK 16:16:16 fertilizer 10 g / plot (100 kg / ha), N2 = NPK 16:16:16 fertilizer 15 g / plot (150 kg / ha), N3 = NPK 16:16:16 fertilizer 20 g / plot (200 kg / ha). The results show that the effectiveness of organic fertilizer from durian peel waste on the growth of sweet corn (Zea mays saccharata Sturt) did not significantly affect plant height and leaf number. Keywords: sweet corn, NPK fertilizer, durian peel waste